Analisis Kesulitan Belajar Siswa dalam Pembelajaran Matematika Materi Bilangan Cacah Sampai 100 Kelas lll Ditinjau dari Gaya Belajar Kolb - Wardani, Elma Kusuma; Salimi, Moch (Universitas Sebelas Maret, 2025)
Students often experience learning difficulties due to lack of focus during learning, caused by concentration disorders from the environment and internal conditions such as fatigue or stress. The purpose of this study is to analyze the learning difficulties experienced by students in learning mathematics division of integers up to 100 in terms of Kolb's learning style. The method used is a literature study by reviewing various journals and books. The research found that: 1) Factors of students' learning difficulties in division of enumerated numbers to 100 in class lll are influenced by internal and external factors. 2) Kolb's learning style (diverger, assimilator, converger, and accommodator) can overcome students' learning difficulties in the material of dividing integers up to 100. Thus, to overcome students' learning difficulties in learning mathematics division of integers up to 100, Kolb's learning style can be used according to each student's ability.Siswa sering mengalami kesulitan belajar karena kurang fokus saat pembelajaran, disebabkan oleh gangguan konsentrasi dari lingkungan dan kondisi internal seperti lelah atau stres. Tujuan dari penelitian ini untuk menganalisis kesulitan belajar yang dialami siswa dalam pembelajaran matematika materi pembagian bilangan cacah sampai 100 ditinjau dari gaya belajar kolb. Metode yang digunakan merupakan studi literatur dengan mengkaji berbagai jurnal dan buku. Penelitian membukitkan bahwa: 1) Faktor kesulitan belajar siswa dalam materi pembagian bilangan cacah sampai 100 kelas lll dipengaruhi oleh faktor internal dan eksternal. 2) Gaya belajar kolb ( diverger, assimilator, converger, dan accommodator ) dapat mengatasi kesulitan belajar siswa dalam materi pembagaian bilangan cacah sampai 100. Dengan demikian untuk mengatasi kesulitan belajar siswa dalam pembelajaran matematika materi pembagian bilangan cacah sampai 100, gaya belajar kolb dapat digunakan dilihat sesuai dengan kemampuan siswa masing-masing.